Nurse educators' perceptions of OSCE as a clinical evaluation method - MM Chabeli (AOSIS, 2001)
The South African Qualifications Authority, and the South African Nursing Council are in pursuit of quality nursing education to enable the learners to practise as independent and autonomous practitioners. The educational programme should focus on the facilitation of critical and reflective thinking skills that will help the learner to make rational decisions and solve problems. A way of achieving this level of functioning is the use of assessment and evaluation methods that measure the learners' clinical competence holistically. This article is focused on the perceptions of twenty nurse educators, purposively selected from three Nursing Colleges affiliated to a university in Gauteng, regarding the use of OSCE (Objective Structured Clinical Examination) as a clinical evaluation method within a qualitative and descriptive research strategy. Three focus group interviews were conducted in different sessions. A descriptive content analysis was used. Trustworthiness was ensured by using Lincoln and Guba's model (1985). The results revealed both positive and negative aspects of OSCE as a clinical evaluation method with regard to: administrative aspects; evaluators; learners; procedures/instruments and evaluation. The conclusion drawn from the related findings is that OSCE does not measure the learners' clinical competence holistically. It is therefore recommended that the identified negative perception be taken as challenges faced by nurse educators and that the positive aspects be strengthened. One way of meeting these recommendations is the use of varied alternative methods for clinical assessment and evaluation that focus on the holistic measurement of the learners' clinical competence.